Comparison of patients with hepatic encephalopathy and those with gastric varices before and after balloon‐occluded retrograde transvenous obliteration. Issue 12 (5th July 2018) - Ishikawa, Tsuyoshi; Sasaki, Ryo; Nishimura, Tatsuro; Matsuda, Takashi; Maeda, Masaki; Iwamoto, Takuya; Saeki, Issei; Hidaka, Isao; Takami, Taro; Sakaida, Isao
Abstract : Aim: To compare the clinical characteristics of patients with hepatic encephalopathy (HE) and those with gastric varices (GV) before and after balloon‐occluded retrograde transvenous obliteration (BRTO). Methods: Eighty cirrhotic patients who underwent BRTO, including 42 men and 38 women, and whose mean age was 68 years, comprised the HE ( n = 18) and GV ( n = 62) groups. The patients' data before and 1 month after BRTO were analyzed. Results: Before BRTO, the groups did not differ in their portal flow volume (PFV) or hepatic venous pressure gradient (HVPG). The portal vein (PV) was narrower and the splenic vein (SpV) was wider in the HE group than in the GV group. The SpV flow was hepatofugal in 75.0% of HE patients and hepatopetal in 92.6% of GV patients. The Child–Pugh (CP) score of the HE group was significantly higher than that of the GV group pre‐BRTO. After BRTO, the PFV and HVPG increases in the HE group equaled those in the GV group, and the PV dilation was similar in both groups. Conversely, the SpV was significantly contracted for HE patients, but significantly dilated for GV patients. Postoperatively, the SpV flow was hepatopetal in all patients. Compared to that in the GV group, the CP score decreased markedly in the HE group, and no significant increases in complications occurred post‐BRTO for HE patients. Conclusions: The HE patients showed distinct portal‐splenic hemodynamics before and after BRTO. Balloon‐occluded retrograde transvenous obliteration markedly improved hepatic function in the HE group compared with the GV group.